Co‐Existing Non‐Occlusive Splenic Vein and Superior Mesenteric Vein Thrombosis in an Acute Necrotic Pancreatitis Patient—A Case Report - Andreea Irina Ghiță; Arina Ilinca Gheorghe; Georgiana Elena Beteringhe; Andreea Ramona Treteanu; Mihai Radu Pahomeanu (Clinical Case Reports)
ABSTRACT Case report of a case of acute pancreatitis (AP) at a patient previously known with essential thrombocytosis (ET). The most redoubtable complications of AP in this case were: pancreatic necrosis and splahnic vein thrombosis (SVT). Patient was followed‐up for 3 months with complete resolution of SVT under anticoagulation. As far as we know this is the first case ever published suffering simultaneously from AP and ET, both conditions known for their increased risk of developing thrombi.